Beneficial Effects of Liquid Crystalline Phases in Solid‐State Dye‐Sensitized Solar Cells. Issue 5 (19th February 2013) - Costa, Rubén D.; Werner, Fabian; Wang, Xinjiao; Grönninger, Philipp; Feihl, Sebastian; Kohler, Florian T. U.; Wasserscheid, Peter; Hibler, Susanne; Beranek, Radim; Meyer, Karsten; Guldi, Dirk M.
Abstract Two novel double‐alkyl functionalized imidazolium ionic liquid crystals have successfully been utilized to demonstrate the benefits of the liquid crystalline phase on the ssDSSC performance. In particular, a good balance between dye regeneration and hole transport is only realized in the liquid crystalline phase. Devices that employ a single component ionic liquid based electrolyte show a remarkably stable efficiency during 1000 h under outdoor operation temperature conditions and 1 sun illumination.